Curation and annotation for BioModels Database, a resource of published quantitative kinetic models - Vijayalakshmi, Chelliah; Endler, Lukas; Laibe, Camille; Li, Chen; Le Novère, Nicolas (Nature precedings, 2009)
BioModels Database ("http://www.ebi.ac.uk/biomodels/":http://www.ebi.ac.uk/biomodels/) is a free resource for storing, viewing and retrieving published, peer-reviewed, quantitative models of biochemical and cellular systems. As a storage format, BioModels Database uses the Systems Biology Markup Language (SBML), but also allows submission and export of models in various other commonly used formats.To offer scientists reliable information, models are curated to comply with the MIRIAM (Minimal Information Requested In the Annotation of biochemical Models) standard. This curation process involves verification of the model structure, the parameter and variable values and its mathematical relations. Furthermore reproduction of results in the reference publication is checked.The different elements of the models are extensively annotated with references to controlled vocabularies and links to other databases, to allow for identification and search. Those references and links are provided in the exported SBML files as a URN (Uniform Resource Name), identifying the data-type and the data-set, and a qualifier, indicating the relation between the element and the referenced data-set. The URNs follow the MIRIAM scheme and are resolved, for instance to URLs, using the Web Services of MIRIAM Resources ("http://www.ebi.ac.uk/miriam/":http://www.ebi.ac.uk/miriam/).